Pengaruh Kepemimpinan, Motivasi, Loyalitas Kerja, Kompetensi Terhadap Kinerja Aparatur Sipil Negara Dinas Lingkungan Hidup Kabupaten Bone - Andi Djalante (Program Pascasarjana STIE Amkop Makassar, 2022)
Abstract The purpose of this study was to analyze whether the influence of motivation, work loyalty, competence, leadership on the performance of the state civil apparatus of the environmental service of Bone Regency. Either partially or simultaneously, and among the four independent variables above, it will also be investigated which one has the most dominant effect. The number of samples used at the research locus were all employees, totaling 39 State Civil Apparatuses, all of whom were civil servants. From the research, it can be proven that partially leadership and competence have a negative effect on the performance of the state civil apparatus, then the partial test on motivation and work loyalty can be proven to have a positive and significant effect on the performance of the state civil apparatus at the Bone Regency Environmental Service. Then the results of this research also provide evidence that work loyalty is the variable that has the most dominant influence on the performance of state civil servants at the Bone Regency Environmental Service. Furthermore, in the determination test, the coefficient of determination was obtained at 97.8% which indicates that this research model can explain that employee performance is influenced by 97.8% by the variables of motivation, work loyalty, competence, leadership and 2.2% is influenced by variables others that were not investigated in this study. Keywords: Motivation, Work Loyalty, Competence, Leadership, Performance